Reality In Animation: A Cultural Studies Point of View - Marthana Yusa, I Made; Ardhana, I Ketut; Darma Putra, I Nyoman; Gede Pujaastawa, Ida Bagus (Eduvest - Journal of Universal Studies, 2023)
This research discerns at animation as a text by focusing on the investigation of the aspects and concepts that define a reality in the world of animation. By looking at the reality in the animation, clues and texts can be generated that contribute to understanding the postmodernity framework and the concept of representation from the point of view of cultural studies. This qualitative research uses a cultural studies approach, with the method of intertext analysis of texts from literature studies and interviews with expert source persons in the field of animation. Postmodernism and hyper-reality theories are used eclectically with the concepts of simulation and representation to support hermeneutic reasoning models. This research resulted in the formulation of the concept of reality in animation with the point of view of cultural studies which includes a description of the concept of reality in the presence of animated works, the components of reality in animation, and the meaning of reality in animation